Systems engineering: Driving green economy and renewable energy transitions - Zárate, Alex (2024)
This chapter provides a synthesis of the key issues related to systems engineering and its contribution to the green economy and energy sustainability. It explores essential concepts in sustainable energy systems, renewable technologies, energy efficiency, and highlights global challenges in cooperation, emerging technologies, education, policy and regulations, and investment in sustainable infrastructure. Systems engineering consolidates its position as a fundamental pillar.